1-2 Timothy, Titus - Huizenga, Annette Bourland (Book collections on Project MUSE., 2016)
The author of 1 Timothy, 2 Timothy, and Titus argues in favor of a "traditional" Greco-Roman gender ideology: that because men and women are biologically different, they ought to behave differently in the family and society. His gender-specific beliefs carry over into his teachings for the house churches, where only free married men are eligible to serve as leaders, teachers, and preachers, while women are expected to take up the subordinate female domestic roles of wife, mother, and household manager. This volume encourages a deeper engagement with the difficult issues-gender, race, and power-raised by these letters. By studying the Pastoral Letters with our minds sharpened and our hearts turned toward a generous freedom, we can struggle most productively with the influences of their teachings, past and present, and we can create a future church and a future world that are more just, truly inclusive, and indelibly marked by God's grace. (Publisher).